Complete Mitochondrial Genomes of Metcalfa pruinosa and Salurnis marginella (Hemiptera: Flatidae): Genomic Comparison and Phylogenetic Inference in Fulgoroidea - Min Jee Kim; Keon Hee Lee; Jeong Sun Park; Jun Seong Jeong; Na Ra Jeong; Wonhoon Lee; Iksoo Kim (Current Issues in Molecular Biology, 2021)
The complete mitochondrial genomes (mitogenomes) of two DNA barcode-defined haplotypes of Metcalfa pruinosa and one of Salurnis marginella (Hemiptera: Flatidae) were sequenced and compared to those of other Fulgoroidea species. Furthermore, the mitogenome sequences were used to reconstruct phylogenetic relationships among fulgoroid families. The three mitogenomes, including that of the available species of Flatidae, commonly possessed distinctive structures in the 1702–1836 bp A+T-rich region, such as two repeat regions at each end and a large centered nonrepeat region. All members of the superfamily Fulgoroidea, including the Flatidae, consistently possessed a motiflike sequence (TAGTA) at the ND1 and trnS2 junction. The phylogenetic analyses consistently recovered the familial relationships of (((((Ricaniidae + Issidae) + Flatidae) + Fulgoridae) + Achilidae) + Derbidae) in the amino acid-based analysis, with the placement of Cixiidae and Delphacidae as the earliest-derived lineages of fulgoroid families, whereas the monophyly of Delphacidae was not congruent between tree-constructing algorithms.